Accept, distract, or reframe? An exploratory experimental comparison of strategies for coping with intrusive body image thoughts in anorexia nervosa and body dysmorphic disorder. Issue 3 (28th February 2015) - Hartmann, Andrea S.; Thomas, Jennifer J.; Greenberg, Jennifer L.; Rosenfield, Elizabeth H.; Wilhelm, Sabine
Abstract: Negative body image is the hallmark of anorexia nervosa (AN) and body dysmorphic disorder (BDD). One aspect of body image, appearance-related thoughts, have shown to be a major contributor to relapse, thus further investigation of successful treatment strategies targeting these maladaptive thoughts are warranted. The present study tested an acceptance/mindfulness (AC), a cognitive restructuring (CR), and a distraction strategy with regard to their short-term effectiveness of reducing the frequency of thought occurrence and associated outcomes in participants with AN ( n =20), BDD ( n =21), and healthy controls (HC; n =22). Although all strategies led to a significant reduction of thought frequency, there was no group×strategy interaction effect in their reduction. Positive affect increased in the BDD group through the AC strategy, but decreased in healthy controls. Acceptance of the thought increased in the CR strategy in AN, whereas that strategy seemed to work least for BDD. Healthy controls showed most acceptance when using distraction. Taken together, the study suggests that all strategies might have their benefits and that it might be worthwhile further investigating differential indication of the strategies with regard to diagnosis and individual factors. Highlights: All strategies led to a reduction in thought frequency, no strategy proved to be superior for any group. In BDD the acceptance strategy was beneficial for positive affect, whereas for HC it was detrimental. The groups benefitted differently in their acceptance of the thoughts depending on strategies used. Acceptance may be a valuable alternative to CR for body-image related thoughts.